Dividend Policy Sebagai Intervening Hubungan Rasio Keuangan Terhadap Firm Value di BEI - Marhaenis Handoko Putro, Guruh; Wany, Eva (Akuntansi: Jurnal Akuntansi Integratif, 2021)
Abstract The research objective is to examine the effect of liquidity, leverage and profitability on firm value through the intervening dividend policy variable. The sampling method used is purposive sampling method. The data analysis method in this research uses path analysis. The results of the research reveal that liquidity and profitability do not have a positive and significant effect on dividend policy. Leverage has a positive and significant effect on dividend policy. Liquidity and profitability do not have a positive and significant effect on firm value. Leverage has a positive and significant effect on firm value. Dividend policy has no positive and significant effect on firm value. Liquidity and leverage indirectly have no positive and significant effect on firm value through dividend policy dividend. While profitability indirect but significant positive effect on firm value through dividend policy.